User Interface Design for Gamification of Ethnomathematics Data/Content Based on Challenges of Local Wisdom - Lokasanti, I Ketut; Divayana, Dewa Gede Hendra; Sudatha, I Gde Wawan; Warpala, I Wayan Sukra (Bright Publisher, 2026)
Not all students possess the capability to effectively solve problems in accordance with the materials they have studied, both theoretically and practically, in reference to the realities of everyday life. This phenomenon is particularly evident in many junior high schools in Bali, especially within the context of mathematics education. Consequently, there is a pressing need for innovative breakthroughs to address these challenges. One such approach involves the development of gamified mathematics learning based on local Balinese wisdom. The primary objective of this research is to demonstrate the design of a user interface for gamified ethnomathematics data/content grounded in the challenges of local Balinese wisdom. This research adopts a development approach, employing the Borg and Gall model, which focuses solely on the stages of design development, initial testing, and revisions based on the outcomes of the initial trials. The subjects involved in the initial testing of the user interface design include two informatics experts, two education specialists, 40 educational technology evaluators, and 20 public junior high school teachers in Bali, particularly from the southern region. Data collection tools utilized an instrument in the form of a questionnaire consisting of 15 items related to the design of the user interface for gamified ethnomathematics data/content based on the challenges of local Balinese wisdom. The analysis of the collected data employed quantitative descriptive techniques.The research findings indicate that the quality of the user interface design is within the 'good' category, with an average percentage of 87.19%. The contribution and the most obvious implications of this research is that it can clearly demonstrate the form of gamification user interface design. Design that contains aspects of game data/content that internalize the challenges of the reality of Balinese local wisdom so that it can improve students' critical thinking skills in solving complex problems of everyday life.